A briefe concordance to the Bible of the last translation. Seruing for the more easie finding out of the most vsefull places therein contained. Alphabetically digested, and allowed by authoritie to be printed, and bound with the Bible in all volumes. [electronic resource] : (1630)
Summary goes here